(untitled) (International Journal of Communication Systems and Network Technologies, 2013)
In this paper an Artificial neural network (ANN) design technique for a Stub Microstrip Band-pass filter is presented. Essential dimensions of the microstrip filter layout are used to get the relationship in the input-outputs of ANN model. This paper presents the design and analysis of Stub Microstrip Band-pass Filter at mid-band frequency 1.8 GHz which gives improved bandwidth and minimum insertion loss of -0.5899 dB and return loss of -36.67 dB. Also artificial neural network architecture is proposed to determine the Magnitude variation of scattering parameters (S-parameters) of these Microstrip Band-pass filters for various dimensions. When the ANN model is produced, it has been exposed to be as exact and veracious as an EM simulator and it is computationally more effective in the design. The simulation is performed using the commercial software IE3D 14.1 and ANN Training of S-Parameters are performed in MATLAB 7.1 Software.